ANALISIS PENGGUNAAN BUKU DIGITAL KATEGORI B2 TERHADAP KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS II SD MENGGUNAKAN PENDEKATAN DEEP LEARNING - Agustianingrum, Ajeng; Aryanto, Sani; Awiria (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness of using Digital Books Category B2 through the Deep Learning Approach in improving reading comprehension skills of second-grade elementary school students. The main issue raised is the gap between technical reading skills (decoding) and understanding of deep meaning during the literacy transition phase. Using a descriptive qualitative approach, the study involved 30 second-grade students in the 2025/2026 academic year. Data were collected through observation, interviews, and assessment of learning outcomes regarding the use of the digital media